Futures : the great turn - Dartiguepeyrou, Carine; Saloff Coste, Michel (London : ISTE Ltd ; Hoboken, NJ : John Wiley & Sons, Inc., 2023)
In the same way as there are many futures, not just one, there are many ways to conceive and practice foresight. The challenge of the great turning point of our civilization is to free ourselves from our prejudices in order to imagine and build desirable futures. The process is, by nature, ethical and prospective. In a complex, uncertain and geopolitically transforming world, we must be open to the diversity of cultures and the different perceptions of the future. This requires us to reflect on the purpose and means of our societies. Futures proposes different cultural and ethical views on civilizational transformation by offering a rare, transnational panorama of the visions of the future in a European, American and Chinese context. Through numerous examples, this book illustrates how foresight is practiced and what this can achieve in strategic terms.
6.3. Foresight and support for innovation in companies -- 6.3.1. Analysis of the innovative ecosystem -- 6.3.2. Consequences of the innovative investment -- 6.3.3. Foresight approach and radical innovation -- 6.4. Conclusion -- Chapter 7. Acting and Evaluating through Values in the Long Term -- 7.1. The question of foresight applied to territories -- 7.2. Initiating change with action research -- 7.2.1. Better understanding of the issues at work -- 7.2.2. From the initiation of the project to the collective construction process
Includes bibliographical references and index.
7.2.3. Getting to grips with the subject: integrating biodiversity? Field surveys
Description based on online resource; title from digital title page (viewed on August 16, 2023).
John Wiley and Sons
Keywords: Organizational change -- Forecasting; Twenty-first century -- Forecasts; Changement organisationnel; v; Organizational change -- Forecasting; Twenty-first century; Forecasts